“La reparación económica a los titulares del derecho vulnerado en las garantías jurisdiccionales” - Cojitambo Sandoval, Luis Ángel (2021)
This investigation submitted under the thesis modality refers to a legal problem that deserves to be transformed to solve and overcome the socio- legal problem identified in Article Art. 19 of the Organic Law on Jurisdictional Guarantees and Constitutional Control, noting that when part of the reparation, for any reason, involves payment in cash to the affected person or holder of the violated right, the determination of the amount shall be dealt with in summary verbal trial before the same judge or judge, if any against an individual; and in administrative litigation if it were against the State; procedure that is inconsistent with article (a) of article 2 of Article 86 of the Constitution of the Republic of Ecuador, which stipulates that jurisdictional guarantees will be dealt with in a simple, prompt and effective procedure, in accordance with Article 6 of the Organic Law on Jurisdictional Guarantees and Constitutional Control, which establishes as one of the purposes of judicial guarantees the comprehensive reparation of damage caused by its violation , a mandate that is limited in Article 19 by establishing the start of a new process for the realization of economic redress. So it is necessary to reform the Organic Law on Jurisdictional Guarantees and Constitutional Control incorporating that for the determination of the amount of economic reparation for violation of constitutional rights it must be dealt with before the same Judge with constitutional powers that knows and has determined the violation of constitutional rights, without considering whether the shareholding is a particular person or representative of a public institution.